The interconnectedness of culture, language, and intercultural communication: A critical review - Buelt, Florian; Chuang, Hsueh-Hua (Global Journal of Social Sciences Studies, 2025)
This paper critically examines the evolving conceptualizations of culture and their impact on language and intercultural communication. Tracing the historical evolution of cultural theory, it highlights the shift from static, essentialist definitions to more dynamic perspectives. The analysis draws on key theoretical frameworks, including categorization of culture as product, discourse, practice, ideology, and globalization, to interrogate how culture is produced, communicated, and enforced. Particular focus is given to the role of language as a driver for cultural expression, a means for negotiating cultural values and identities, and a key component of intercultural competence. Definitions of cultures and their interconnectedness with language and intercultural communication are connected, especially in view of an increasingly globalized world. Shifting conceptualizations of culture emerge and their implications on both languaguage use and broad communication between various members of society are presented. The paper concludes by emphasizing the importance of understanding the fluid and interconnected nature of culture, language, and the intercultural in an increasingly globalized world, advocating for a critical approach that acknowledges culturally and linguistically inherent power dynamics.